PHYSICAL PROPERTIES OF A CLASS OF SPHERICALLY SYMMETRIC PERFECT FLUID DISTRIBUTIONS IN NONCOMOVING COORDINATES - Knutsen, H. (Одеські астрономічні публікації, 2017)
The physical properties of an exact solution of Einstein’s field equations are examined. This spherically symmetric perfect fluid solution contains expansion, acceleration and shear. There exist models with regions of spacetime where the pressure and the density are positive and the dominant energy condition and the causality condition are also fulfilled. Moreover, the pressure and the density gradients are equal. The mass function is zero at the origin where there is Lorentz-Minkowski geometry and no trapped surface exists.